Facile fabrication of robust, hyaluronic acid-surfaced and disulfide-crosslinked PLGA nanoparticles for tumor-targeted and reduction-triggered release of docetaxel. (15th April 2021) - Wang, Xiuxiu; Cheng, Ru; Zhong, Zhiyuan
Abstract: It is highly tempting to develop high-efficacy targeted nanotherapeutics based on FDA approved polymers like PLGA. Herein, we describe facile fabrication of robust, hyaluronic acid-surfaced and disulfide-crosslinked star-PLGA nanoparticles (HA-sPLGA XNPs) for targeted and reduction-triggered release of docetaxel (DTX), achieving markedly enhanced treatment of A549 lung tumor in vivo . HA-sPLGA XNPs carrying 5.2 wt.% DTX (DTX-HA-sPLGA XNPs) had a size of 105.5 ± 0.5 nm and great stability while almost completely released DTX under 10 mM glutathione. Confocal and flow cytometry experiments revealed fast cellular uptake of HA-sPLGA XNPs by CD44-overexpressing A549 cells. DTX-HA-sPLGA XNPs held much higher potency to A549 cells than DTX-loaded HA-surfaced and non-crosslinked star-PLGA nanoparticles (DTX-HA-sPLGA NPs), DTX-loaded HA-surfaced and non-crosslinked linear-PLGA nanoparticles (DTX-HA-lPLGA NPs), and free DTX (IC50 = 0.18 versus 0.38, 1.21 and 0.83 µg DTX equiv./mL). Intriguingly, DTX-HA-sPLGA XNPs revealed a prolonged elimination half-life of 4.18 h and notable accretion of 9.49%ID/g in A549 tumor after 8 h injection. Accordingly, DTX-HA-sPLGA XNPs demonstrated significantly better suppression of subcutaneous A549 lung tumor than DTX-HA-PLGA NPs, DTX-HA-lPLGA NPs, and free DTX controls. HA-sPLGA XNPs with low toxicity and multi-functionality appear to be a unique targeted vehicle for chemotherapy of CD44-overexpressing tumors. Statement of significance: PLGA nanoparticles with superior safety and biodegradability are among the most advanced vehicles for therapeutic delivery. The efficacy of nanomedicines based on PLGA is, however, suboptimal, due to poor tumor cell selectivity and uptake, drug leakage, and slow drug release at the pathological site. It is highly desired to develop functional PLGA nanoparticles to improve their tumor-targeting ability and therapeutic efficacy. The sophisticated fabrication and potential toxicity concerns of reported novel PLGA nanoformulations, nevertheless, preclude their clinical translation. Here, we developed hyaluronic acid-surfaced and disulfide-crosslinked star-PLGA nanoparticles (HA-sPLGA XNPs) that enabled stable encapsulation and targeted delivery of docetaxel (DTX) to CD44+ A549 lung cancer cells in vitro and in vivo, affording markedly improved tumor accumulation and repression and lower side effects compared with free DTX control. Importantly, HA-sPLGA XNPs are based on fully biocompatible materials and comparably simple to fabricate. The evident tumor targetability and safety makes HA-sPLGA XNPs a unique and potentially translatable platform for chemotherapy of CD44+ cancers. Graphical abstract: Image, graphical abstract